PERILAKU IBU DALAM PENCEGAHAN KEKAMBUHAN PNEUMONIA PADA BAYI DAN BALITA DI KOTA SEMARANG - Cindy Adhitya Maharani; Syamsulhuda Budi Musthofa; Besar Tirto Husodo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Pneumonia is an inflammation which occurs in the lungs caused by infection. Pneumonia can affect to all age groups but it becomes one of the main causes of mortality in children under five years old. Penumonia reccurence is possible to happen after the first episode has been cured. Mothers have important role in children's lives, which includes maintaining their health by recognizing signs of disease in children and seeking medical help. This study aimed to analyze the factors associated with mother’s behavior in preventing recurrence of pneumonia in children under five years old in Semarang. The study used a cross sectional study design. The population of this study were mothers of children under five years old with a history of pneumonia in Semarang. Sampling was chosen with a multi stage random sampling technique and 90 samples were colected. Data were analysed with univariate and bivariate analysis. The results from the study showed that most of the participants didn’t do pneumonia reccurence prevention (60,0%). The chi square test results showed perceived severity (p=0,037), perceived benefits (p=0,000), perceived barriers (0.010), and self-efficacy (p=0,00) had a significant relationship with mother behaviors in preventing pneumonia recurrence in children under five years old in Semarang while perceived susceptibility did not (p=0,448). Providing information about the benefits of pneumonia prevention in children under five years old needs to be done to community to prevent child mortality caused by pneumonia.